Argon plasma coagulation for the treatment of hereditary hemorrhagic telangiectasia - Bergler, Wolfgang; Riedel, Frank; Baker Schreyer, Antonio; Mattinger, Cathrine; Hörmann, Karl (The laryngoscope, 1999)
Objectives: Patients with (HHT) often suffer from recurrent epistaxis, which poses considerable therapeutic problems. Theoretical considerations render argon plasma coagulation (APC) a promising new therapeutic approach. Study Design: In a prospective study 12 patients (aged 8-68 y) who presented with a long history of treatment for epistaxis were treated with telangiectasia in the nasal mucosa. After 2 weeks and again after 4 months the treatment results were evaluated by questionnaire. Methods: APC is based on high-frequency electric energy transmitted through ionized argon gas to the tissue in a noncontact mode. Coagulation and desiccation of tissue are limited to 1 to 2 mm of penetration and therefore risk of tissue damage is low. Coagulative effects are best in tissue with high electrical conductivity, especially blood vessels. Results: All patients were satisfied with the postoperative results. Frequency and intensity of bleeding were significantly reduced. All patients reported better postoperative results than with any other treatment they had received previously. Conclusion: First clinical experience shows that APC is a useful alternative for the treatment of telangiectasia in the nasal mucosa and should be a therapeutic option for this disease.
Elektronische Reproduktion der Druckausgabe
Gesehen am 10.05.2022